A functional index model for dynamically evaluating China's energy security. (December 2020) - Wang, Deqing; Tian, Sihua; Fang, Lei; Xu, Yan
Abstract: With the aim of overcoming the shortcomings of the conventional energy security index (ESI) used in dynamic assessment of energy security, the present study introduces the functional data analysis method into ESI construction and establishes a dynamic energy security index (DESI) model. The DESI is a generalization of the conventional ESI with a dynamic weighting mechanism in a continuous time domain. In the DESI model, every normalized indicator within three dimensions — energy supply, energy consumption and environmental — is smoothed into a continuous curve, and the changes in its importance are reflected objectively by functional information entropy weights with dynamic information updating. Whereas the three sub-index curves with different importance are distinguished via assigning different weights according to the special national circumstances. The methods of generating a curve for single indicator, sub-index curves, and dyna mic weighting curves are discussed in detail, and the robustness of weighting and aggregation choice in DESI is tested using sensitive analysis. Results of applying DESI to evaluate China's energy security show that the overall changes of China's energy security have undergone a W-shaped fluctuation. To ensure consistently high levels of energy security, the government should focus on oil supply and renewable energy technologies. Highlights: This paper introduces the FDA methods into energy security evaluation research. A dynamic energy security index model based on FDA (DESI)was proposed. The changes of China's energy security underwent a W-shaped fluctuation. Government should focus on the crude oil and renewable to ensure consistently high levels of energy security.